2007
DOI: 10.1074/jbc.m703132200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress-mediated Mesangial Cell Proliferation Requires RAC-1/Reactive Oxygen Species Production and β4 Integrin Expression

Abstract: Lipid abnormalities and oxidative stress, by stimulating mesangial cell (MC) proliferation, can contribute to the development of diabetes-associated renal disease. In this study we investigated the molecular events elicited by oxidized low density lipoproteins (ox-LDL) in MC. We demonstrate that in MC cultured in the presence of ox-LDL, survival and mitogenic signals on Akt and Erk1/2 MAPK pathways are induced, respectively. Moreover, as shown by the expression of the dominant negative Rac-1 construct, we firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…In accordance with our present findings, a previous study showed that oxidative stress-mediated glomerulosclerosis required Rac1 activation [32]. Rac1 is also reported to be upregulated in a tacrolimus-induced renal injury model [33].…”
Section: Rac1 Activation In Prepubertal Ratssupporting
confidence: 92%
“…In accordance with our present findings, a previous study showed that oxidative stress-mediated glomerulosclerosis required Rac1 activation [32]. Rac1 is also reported to be upregulated in a tacrolimus-induced renal injury model [33].…”
Section: Rac1 Activation In Prepubertal Ratssupporting
confidence: 92%
“…CD36 has been identified as a member of scavenger receptor B family that may be the main receptor for modified low-density lipoprotein uptake in mesangial cells [18]. Lectin-like oxidized LOX-1, which was originally identified as a receptor for oxidized lowdensity lipoprotein expressed in vascular endothelial cells, was also found in mesangial cells [19,20]. SRBI was reported to be a cell surface receptor that binds HDL and plays an important role in mediating selective uptake of cholesteryl esters in proximal tubules [21], but there is no evidence to confirm its expression in mesangial cells.…”
Section: Oxidized Hdl Upregulates Cd36 and Lox-1 Expression Of Rmcsmentioning
confidence: 99%
“…[28][29][30] Oxidative stress can activate MAP kinase signaling, which ultimately contributes to the proliferation of mesangial cells in the setting of diabetic nephropathy. 31 Mesangial cell proliferation is also involved in the development of CAN. Therefore, we next determined whether HW administration could suppress MAP kinase activation in the kidney allografts.…”
Section: Oral Administration Of Hw Prevents the Progression Of Canmentioning
confidence: 99%